The Expressions Of Ngalem In The Javanese Society In Kebumen Regency (Wanastra: Jurnal Bahasa dan Sastra, 2024)
This research is based on using "ngalem" or praising oral speech in daily communication. “Ngalem” is an expression to show admiration for other people. Nowadays, the use of this term is rarely used in Javanese society. This research aims to describe and explain the metaphors found in Javanese speech when someone "ngalem" or praises another person. Next, provide data using the listen and note method. There are several findings, first, "ngalem" or praise is usually intended to praise the beauty of male and female body parts including the head, body, hands, and feet. Second, the type of metaphor that dominates is anthropomorphic metaphor. "ngalem" tends to match parts of the human body with inanimate objects. Third, the animal metaphor type is used to describe a beautiful neck as coiled like a snake, while the synesthetic metaphor is used to "smile" at the beauty of the lips. Some informants still remember this expression but tend not to understand its meaning. Some informants also no longer introduce these expressions to their children or grandchildren. This research illustrates the Javanese community's declining interest in maintaining and passing on the language to the generations below.
Keywords: Javanese language; oral tradition; "ngalem" or praise